Abdominal heterotopic pregnancy after in vitro fertilization and embryo transfer following bilateral salpingectomy: A case report and literature review - Liu, Yifeng; Li, Yu; Li, Keting; Li, Shuangdi (Frontiers in Reproductive Health, 2022)
Background: Risk of heterotopic pregnancy following bilateral salpingectomy has increased considerably due to the widespread use of assisted reproductive technology. Poor understanding of this condition often causes delayed or missed diagnosis. Objective: In this report, we describe the case of a 30-year-old pregnant woman with lower abdominal pain lasting for half a day and a history of bilateral salpingectomy. Two embryos had been transferred 21 days preceding her presentation. Methods: Case report. Results: Laparoscopic surgery revealed intraperitoneal hemorrhage and proper ovarian ligament pregnancy confirmed by histopathology. Viable intrauterine pregnancy was verified 3 days later by ultrasound examination. Conclusion: Heterotopic pregnancy is a serious condition that may be life-threatening. Clinicians should be aware of the potential for heterotopic pregnancy in patients receiving in vitro fertilization and embryo transfer after bilateral salpingectomy.